Intracoronary imaging-guided rotational atherectomy combined with intravascular lithotripsy in the treatment of severe coronary artery calcification—A case report - Cui, Fengwen; Tong, Yaliang; Liu, Guohui; Zhang, Wenqi; Liu, Kun; Si, Daoyuan; He, Yuquan (Frontiers in Cardiovascular Medicine, 2023)
Background: Severe coronary artery calcification increases the difficulty of percutaneous coronary intervention procedures and impairs stent expansion. Herein, we report a case of a patient who was successfully treated with rotational atherectomy using a stepped burr strategy combined with intravascular lithotripsy for plaque modification under intracoronary imaging. Case Summary: A 65-year-old woman presented to our hospital with recurrent chest pain evolving for 1 year. Coronary angiography showed approximately 80% stenosis of the proximal mid-left anterior descending artery. Intravascular ultrasound (IVUS) and optical coherence tomography (OCT) revealed a 360° annular calcification. The calcification was rotablated with 1.5 and 1.75 burrs, and the lesion was undilatable with a 3.0-mm non-compliant balloon at 14 atm. Subsequently, the intravascular lithotripsy was reset for the modification of the calcified lesion. A shockwave balloon measuring 3.0 × 12 mm was delivered, and 40 pulses were performed at 6 atm. Intravascular imaging modalities (IVUS and OCT) revealed a circumferential calcified plaque with deep fractures. After post-balloon expansion followed by drug-eluting stent placement with a final stent expansion of 84%, there were no intraoperative complications and no major adverse cardiovascular events within 90 days postoperatively. Conclusion: A combination of rotational atherectomy and intravascular lithotripsy may be an effective and complementary strategy for the treatment of severely calcified lesions that cannot be resolved using a single procedure. However, more clinical studies are required to clarify this finding.